PENGEMBANGAN BUKU PENUNJANG TEMATIK TERPADU BERBASIS KETERAMPILAN PROSES TEMA INDAHNYA KEBERSAMAAN UNTUK KELAS 4 SD/MI - Rizka Nur Oktaviani; Putri Kurnianingtyas (Taman Cendekia: Jurnal Pendidikan Ke-SD-an, 2020)
The integrated thematic supporting book based on process skills that will be developedÂ  to reduce students' dependence on teachers, provide direct learning experiences, can be a tool for students to learn about themselves and the environment, and can be applied independently by students to solve problems they meet in daily life. This type of research is categorized as a research development with a 4-D model that are defining, designing, developing, and distributing. The subjects in this study are integrated thematic support books based on process skills that are tested on fourth grade students in elementary school. The limited test is carried out on 10 students in grade IV Hidayatul Mubtadiin Pasuruan City who are randomly selected. Meanwhile, the field trial is conducted in three classes IV A Hidayatul Mubtadiin Pasuruan City, which Consist of 25 students. The research data are validity data, practicality data, and effectiveness data from integrated thematic supporting books. Furthermore, data collection is done through observation, questionnaires, and tests. Data Analysis is done by analyzing the level of validity and reliability, analyzing the level of difficulty, analyzing obstacles, analyzing the results of process skills, and analyzing student responses. The results obtained by the validity level of 3.63 and reliability of 0.97. Meanwhile, the level of difficulty of the book based on the percentage of difficult words, difficult sentences and difficult to understand images are 1.03%, 2.18%, and 10.83, respectively. The result of students 'process skills is analyzed with the t-test formula on the result of the students' pretest and posttest shows that the value of sig. (2- tailed) is 0,000. Because the value of sig. sig. (2-tailed) <0.05, it can be concluded that there are differences in the significance and response of students to the use of an overall book average of 97.73% which means the book is interesting.